Balancing Stability and Profitability: The Evolution of Regulatory Frameworks and Central Bank Policies Post-2008 Financial Crisis - Du, Runping; Du, Qingxiao (International Journal of Social Sciences and Public Administration, 2025)
This paper explores the evolving role of regulatory frameworks and central banks in safeguarding financial institutions and overall economic stability, particularly in the aftermath of the 2008 subprime loan crisis. It examines how regulatory measures such as Basel III have reshaped financial institutions’ approaches to capital adequacy, liquidity management, and risk sensitivity. Additionally, it delves into the conflicts between regulatory bodies and shareholders, highlighting the challenges of balancing stability with profitability. Through a detailed analysis of the impacts of interest rate adjustments on financial institutions, the paper further assesses the effectiveness of central banks’ monetary policies in promoting economic growth while preventing systemic risks. Finally, the paper offers insights into managing liquidity risks and the implications of the "Too Big to Fail" doctrine on financial stability.